Results of the FIRST STEPS study: a randomised controlled trial and economic evaluation of the Group Family Nurse Partnership (gFNP) programme compared to routine care in improving outcomes for high-risk mothers and their children and preventing abuse - Barnes, Jacqueline; Stuart, Jane; Allen, Elizabeth; Petrou, Stavros; Sturgess, Joanna; Barlow, Jane; Macdonald, Geraldine; Spiby, Helen; Aistrop, Dipti; Melhuish, Edward; Kim, Sung Wook; Pink, Joshua; et al. (NIHR Health Technology Assessment Programme, 2017)
Background: Family Nurse Partnership (FNP) is a home-based nurse home-visiting programme to support vulnerable parents. Group FNP (gFNP) has similar aims and materials and was demonstrated to be feasible in implementation evaluations. Objectives: To determine whether gFNP, compared to usual care, could reduce risk factors for maltreatment in a vulnerable group and be cost effective. Design: A multi-site randomised controlled parallel-group trial and prospective economic evaluation, with eligible women allocated (minimised by site and maternal age group) to gFNP or usual care. Setting: Community locations in the UK. Participants: Expectant mothers aged <20 with one or more previous live births, or 20–24 with no previous live births and with low educational qualifications, defined as neither Mathematics nor English Language General Certificate of Education (GCSE) at grade C or higher or, if both, no more than four GCSEs at grade C or higher. Intervention: Groups offered from early pregnancy until infants are 12 months old with 44 sessions (14 pregnancy, 30 infancy), delivered to 8-12 women with similar expected delivery dates (EDDs; range 8-10 weeks) by two Family Nurses (FNs), one of whom has notified their intention to practise as a midwife. Main outcome measures: Parenting was assessed by a self-report measure of parenting opinions, the revised Adolescent Adult Parenting Index (AAPI-2) and an objective measure of maternal sensitivity, the CARE index. Cost-effectiveness was primarily expressed in terms of incremental cost per quality -adjusted life year (QALY) gained. Data sources: Interviews with participants at baseline and when infants were two, six and 12 months. Cost information from nurse weekly logs and other service delivery data.